Experimental Research in Earthquake Engineering: EU-SERIES Concluding Workshop - Taucer, Fabio (Springer, 2015)
In this volume, top seismic experts and researchers from Europe and around the world, including the George E. Brown, Jr. Network for Earthquake Engineering Simulation (NEES) in the USA, present the most recent outcome of their work in experimental testing, as well as the results of the transnational access activities of external researchers who have used Europe's seven largest and most advanced seismic testing facilities in the framework of the Seismic Engineering Research Infrastructures for European Synergies (SERIES) Project financed by the European Commission in its 7th Framework Programme (2007-2013). This includes EU’s largest reaction wall facility, EU's four largest shaking table laboratories and its two major centrifuges. The work presented includes state-of-the-art research towards the seismic design, assessment and retrofitting of structures, as well as the development of innovative research toward new fundamental technologies and techniques promoting efficient and joint use of the research infrastructures. The contents of this volume demonstrate the fruits of the effort of the European Commission in supporting research in earthquake engineering.